External Ophthalmomyiasis Due to Dermatobia hominis Masquerading As Orbital Cellulitis. Issue 5 (September 2016) - Alsaif, Norah; Liao, Sophie; Tse, David T.
Abstract : Human parasitization by oestrid flies is a rare occurrence. The authors report a case of ophthalmomyiasis externa caused by Dermatobia hominis infestation in a 10-year-old female. Misdiagnosis resulted in a delay in treatment, which can be potentially devastating in cases of orbital or ocular involvement. The treatment of choice is early surgical removal of the larvae to minimize the inflammatory response and the extent of surgery. Patients should also be screened for multiple sites of cutaneous infestation. When the organism is completely excised, the prognosis is good. Abstract : A case of external ophthalmomyiasis caused by Dermatobia hominis masquerading as orbital cellulitis is presented.Supplemental Digital Content is available in the text.